DISORDERED EATING BEHAVIORS: AN OVERVIEW OF ASIAN CULTURES - Muazzam, Amina; Khalid, Ruhi (Journal of Pakistan Psychiatric Society, 2008)
Disordered eating refers to troublesome eating patterns that are less frequent or less severe than diagnosed eating disorders. The difference between disordered eating and occasional disruption of normal eating patterns is the urgency and the persistence behind the eating behavior. Review of recent researches showed that disordered eating or atypical eating disorder is far more common and widespread than actual eating disorders. A survey of recent research literature shows an alarming rise in eating disorders in South Asian and Islamic countries. The aim of this paper is to highlight disordered eating behaviors in people of Asian cultures especially Pakistan.